Cooperative Extension and teaching at a land-grant university: homeowner and industry perspectives and considerations of lawn and landscape extension resources and authorized crib cards in the classroom - Stanton, Alexander Christopher (Kansas State University, 2024)
Two pillars of public land-grant universities are providing undergraduate and graduate-level education and providing unbiased, research-based educational materials to the public through cooperative extension. Two extension-related surveys were disseminated to explore current lawn and landscape practices and cooperative extension awareness and use of homeowners and industry professionals across multiple states within the U.S. The objectives of both surveys were to attain a better understanding of the challenges in using cooperative extension resources for the lawn and landscape and which delivery methods they would be most likely to use in the future. In Chapter 1, the survey revealed that almost 50% of homeowners reported that family and friends were their primary information source for questions relating to the lawn and landscape while less than 7% reported using cooperative extension resources as their primary information source. However, over 50% of homeowners indicated that they were aware of cooperative extension resources related to the lawn and landscape at little or no cost to them. Chapter 2 revealed that 74% of horticultural industry professionals were aware of cooperative extension resources, and 43% reported that cooperative extension resources and conferences were their primary source of information for horticultural plant management topics. Both surveys revealed that homeowners and industry professionals are aware of cooperative extension resources and their most important considerations for future use were that it has to be easy to find and updated in the past five years. Homeowners and industry professionals both indicated that they would prefer to use video platforms, traditional online extension publications, social media and emailed newsletters when compared to mailed newsletters, phone-based applications, or phone calls/chats with extension staff. Industry professionals also preferred in-person events. Chapter 3 explored the impact of crib cards on student test performance, test anxiety, and study habits. For most students, there was a <2% change in their average test scores when compared to traditional, non-crib card-allowed tests in the same semester. Students did report that the crib card, “help[ed] motivate me to study” and assisted in creating a “plan for what I didn’t know” while studying. Crib cards supported students with a GPA <2.65 the most, while students with a GPA >3.1 were sometimes hindered in performance. Overall, crib cards are another tool that students can use to help them prepare for tests and feel more confident going into the test. While they can hinder some students’ performance, there was often minimal influence on their overall course grade. Crib cards can be offered but should not be required for students to use.
Keywords: Cooperative extension; Crib cards; Horticulture extension